Pengaruh Budaya Terhadap Bahasa Indonesia (Pengaruh Budaya Terhadap Bahasa Indonesia Dikalangan Remaja) - Edi Syahputra; Hafizah Ismayati; Nur Ain Nun; Puspita Naura Maharani (Universitas Dehasen Bengkulu, 2022)
Indonesia is an archipelagic country with diverse tribes and civilizations, hence regional languages abound. Because culture has a strong influence on the Indonesian language, the diminished usage of good Indonesian is also true. The purpose of this research is to discover how much culture has influenced the Indonesian language, particularly among youth. Google Form was the most successful approach utilised in this study. According to the average poll, when a person employs a regional language outside of his area, he feels weird, uncomfortable, and unfamiliar. He speaks fluent Indonesian, but the regional language must be preserved so that it does not become extinct in order to preserve Indonesia's cultural variety.